2022
DOI: 10.1093/ibd/izac165
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Clostridioides difficile Infection After Ileal Pouch-anal Anastomosis in Patients With Chronic Antibiotic-dependent Pouchitis and Crohn’s-like Disease of the Pouch

Abstract: Background Recurrent or chronic antibiotic therapy is a therapeutic hallmark of chronic antibiotic-dependent pouchitis (CADP) or Crohn’s-like disease of the pouch. Antibiotics alter the gut microbiome, which may increase the risk of Clostridioides difficile infection (CDI). The aim of this study was to determine the prevalence of CDI in patients with CADP and Crohn’s-like disease of the pouch. Methods We conducted a retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A study based on administrative data from hospitalized patients with IBD with pouchitis found that the frequency of CDI was 2.6% in admitted patients (41). In addition, the prevalence of CDI in a retrospective cohort of 198 patients with CADP and CLDP was 9.1%, which is comparable with the general IBD population (42). Patients with CDI of the pouch might exhibit more systemic symptoms and higher recurrence rates than non-IPAA patients.…”
Section: Infectious Pouchitismentioning
confidence: 80%
“…A study based on administrative data from hospitalized patients with IBD with pouchitis found that the frequency of CDI was 2.6% in admitted patients (41). In addition, the prevalence of CDI in a retrospective cohort of 198 patients with CADP and CLDP was 9.1%, which is comparable with the general IBD population (42). Patients with CDI of the pouch might exhibit more systemic symptoms and higher recurrence rates than non-IPAA patients.…”
Section: Infectious Pouchitismentioning
confidence: 80%
“…[44][45][46][47] Oral vancomycin has also been used to treat Clostridium difficile-associated pouchitis. 48,49 In a small case series of 41 patients with chronic pouchitis (3 with concurrent PSC) treated with 4 weeks of vancomycin, 21 patients (51%) demonstrated a clinical response, and at 3 and 6 months, 16 of the 21 responders (76%) demonstrated continued response and remained on chronic vancomycin therapy. 50 The therapeutic impact on liver function and inflammation of the prepouch ileum and pouch body treated by oral vancomycin has also been reported.…”
Section: Oral Vancomycinmentioning
confidence: 99%